Hal-Hal Yang Ada Hubungan Dengan Pneumonia Komunitas Di Wilayah Indonesia Dan India Periode Tahun 2009 Sampai Dengan 2021 - Belosiappa, Grasyie Imilia; Murnita, Ika Azdah; Rompegading, A. Machmud (Bosowa Medical Journal, 2023)
Community-Acquired pneumonia is an inflammation of the lung parenchyma or lower respiratory tract caused by microorganisms, namely bacteria, viruses, fungi, parasites and chemicals to physical exposure, such as temperature and radiation with symptoms of high fever accompanied by coughing up phlegm, rapid breathing (breathing frequency > 50 times / minutes), shortness of breath and other symptoms (headache, restlessness and decreased appetite) which can be a major cause of morbidity and mortality in children under five years of age, especially in developing countries. The purpose of this study was to find out things that have a relationship with community-acquired pneumonia in children under five years old in Indonesia and India for the period 2009 to 2021.  The research method used is a systematic review by synthesizing the results obtained from sixteen analytical research journals with a case control research design. The results of research from sixteen research journals that were processed and analyzed showed that there were things that had a relationship with community-acquired pneumonia in children under five years old in Indonesia and India for the period 2009 to 2021, namely, there is a significant relationship between exclusive breastfeeding (p- value 0.000), nutritional status (p-value 0.000), immunization status (p-value 0.000), low birth weight (p-value 0.000) and exposure to cigarette smoke (p-value 0.000) on the incidence of community-acquired pneumonia in children under five years old. The conclusion is that the incidence of community-acquired pneumonia in children under five years old in Indonesia and India for the period 2009 to 2021 has a significant relationship to exclusive breastfeeding, nutritional status, immunization status, low birth weight and exposure to cigarette smoke.